THE TRADE-ENHANCING EFFECT OF NON-TARIFF MEASURES ON VIRGIN OLIVE OIL - Eyal Ronen (International Journal of Food and Agricultural Economics, 2017)
Over the last 15 years, the global trade of virgin olive oil (VOO) seems to face a stringent regulatory regime, mainly through the imposition of TBT and SPS measures. Such a development should have adversely impacted global levels of VOO trade. However, evidence shows that the world's imports of VOO have more than quadrupled in value since 2000. Alongside this trend, the share of VOO imports gradually shifts from traditional sources (mainly EU) to New World producing countries, such as Argentina, Australia, the USA, and Chile. By extracting data from hundreds of NTM regulations, as well as all possible registered bilateral trade flows between 2002 to 2014, this paper aims to empirically explore to what extent particular NTMs impact imports of VOO. The results indicate that while tariffs remain a stringent barrier, most NTMs have a positive impact on imports, rather than enhancing restrictiveness. The paper asserts that the majority of NTMs respond to consumers' demand for higher food safety standards and protection of human health, while increasing available information and transparency. That, in turn, leads to an expansion in the magnitude of imports of VOO products